The COVID-19 Pandemic: Role of dental professionals in a tertiary care hospital setting - Amit Khatri; Tavisha Goyal; Namita Kalra; Rishi Tyagi; Drishti Kaushal; Puja Sabherwal (Arbu Academic Publishing, 2022)
The coronavirus disease which originated in Wuhan, China led to a worldwide pandemic. In India, which harbors the second largest population in the world, it created challenges on multiple fronts. In view of the increasing demand for medical healthcare, dental professionals represent an untapped resource to combat the pandemic. In many countries, dental professionals have risen to the challenge in the fight against COVID-19. This review aims to highlight the experience of dental professionals in a tertiary care hospital designated as a dedicated COVID-19 facility as frontline workers while also providing a perspective on the much larger role a dental professional can play in future pandemics.